0474 The Effects of Chronic Rhinosinusitis and Obstructive Sleep Apnea on Sleep Quality. (27th April 2018) - Bagchi, N; Sanders, H; Chen, Y; Black, K; Twumasi, A; Udasin, I; Harrison, D; Chitkara, N; Rapoport, D M; Ayappa, I; Lu, S; Sunderram, J
Abstract: Introduction: Obstructive Sleep Apnea (OSA) and Chronic Rhinosinusitis (CRS) each negatively impact sleep quality, but their interaction has not been examined. In our World Trade Center (WTC) dust-exposed population with high prevalence of CRS symptoms and OSA we have shown CRS symptoms were an independent risk factor for OSA. This study examines their relative contributions to sleep quality. Methods: CRS symptoms were obtained from 626 WTC (111M/515F, 33–87 yrs, BMI=29.96 ± 5.53 kg/m 2 ) subjects. CRS+ was defined as ≥3 symptoms: facial pain, post nasal drip, nasal congestion, blocked nose, loss of smell, sneezing, sore throat/hoarseness. Difficulties initiating/maintaining sleep and overall quality of sleep were obtained via questionnaire. Functional Outcomes of Sleep Questionnaire (FOSQ) and Epworth Sleepiness Scale (ESS) were administered. Subjects underwent 2-night home sleep test (ARES TM ) and AHI4 (apneas+hypopneas with 4% O2 desaturations) and RDI (apneas+ hypopneas with 4% desaturation or arousal surrogates) were calculated. OSA was defined as AHI4≥5/hr or RDI≥15/hr. Demographic and co-morbid medical condition data were obtained. Results: 443/626 (70.7%) had OSA; Median AHI4=11/hr (IQR 6–20), Median RDI=26/hr (IQR 19–38); 43.6% mild OSA. 274 (43.8%) were CRS+ and 205 (32.9%) subjects had both CRS and OSA. CRS was associated with poor sleep quality (OR 2.39, 95%CI 1.65–3.46, p<.0001), increased sleepiness (OR 2.17, 95%CI 1.54–3.06, p<0.0001), sleep onset insomnia (OR 2.19, 95%CI 1.58–3.03, p=0.03), and sleep maintenance insomnia (OR 2.63, 95%CI 1.73–3.99, p<.0001). FOSQ was worse in CRS+=16.1 ± 3.4 vs CRS-=17.4 ± 3, p<0.001. In contrast, in this population, OSA did not show a significant relationship with any reported sleep quality metrics. CRS+ remained significantly associated with all sleep quality metrics in a model adjusting for not only OSA, but age, BMI, sleep duration, panic, anxiety, and PTSD. Conclusion: In our population with high CRS and OSA prevalence, CRS symptoms were associated with poor sleep quality, increased sleepiness, and sleep maintenance/onset insomnia independent of OSA. This may have been related to predominance of mild OSA. This suggests that when examining sleep complaints, treatment of CRS independent of OSA may be beneficial and should be considered. Support (If Any): U01OH01415, K24HL109156.